(3GdjGbhJg GdVGhjI dHjGf GdehLgGJ GdRGgjIs - (3fhQ GdOjf Hf fYeI Gddg GdMSjfj GdLRGFQjs
(3ChdgG (B:s
(3hHYO, ajbhd GdabjQ fhQGdOjf s
(3BNQgG (B:s
(3GPG GHUQJ ai daXi bUhQkG hVHWkG ai GdHdGZI hGdHjGf s
(3Vef eLehY s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3efWb Ndjd CZG (B15) s
Keywords: (3GdadSaI hGdefWbs